Diseño y construcción de un podómetro - Herrera, Raúl; Quiñones, Ivett; Letechipia, Jorge; Núñez, Lidia (Revista Mexicana de Ingenieria Biomedica, 2003)
A podometer is an instrument to analyze the distribution of applied pressure to the foot sole. Quantitative analysis of pressure information is used for diagnosis, treatment and clinical evaluation of a pacient. Unfortunately, traditional podometers depend heavily on the physician’s experience and ability, what makes the usage of the instrument prone to errors. In this work we describe the process of designing and building a quantitative electronic podometer. The proposed podometer can produce a distribution map of the applied pressures to the foot sole with a higher resolution and sensitivity than traditional qualitative podometers such as the podoscope and ink impressions